Recurrent Urosepsis and Cardiogenic Shock in an Elderly Patient with Pheochromocytoma - Joan Joo-Ching Khoo; Vanessa Shu-Chuan Au; Richard Yuan-Tud Chen (Case Reports in Endocrinology)
Pheochromocytomas are thought to be uncommon in the elderly. However, the prevalence is likely to be higher than reported, as older patients are less likely to be diagnosed due to absence of classical symptoms of sympathetic overactivity and confounding effects of aging, comorbidities, and medications. We describe a hypertensive elderly patient with incidentally diagnosed pheochromocytoma complicated by recurrent urosepsis, cardiomyopathy, and fatal myocardial infarction. Our case demonstrates that, in older hypertensive patients without classical symptoms, orthostatic hypotension and urinary retention, which are common in the elderly, may indicate catecholamine excess and that the deleterious cardiovascular consequences of catecholamine excess in the elderly are not prevented by pharmacological α- and β-blockade.